Validation of the Corona Virus Anxiety Scale on the Arab Environment Using Item Response Theory - Abdullah; A, Alasmari ,; Ibrahim, Q, Hakami,; Bandar,s, Alzahrain,; Izzeldeen, A, Abdullah, (Journal of Ecohumanism, 2024)
This study uses exploratory factor analysis and item response theory (IRT) to analyze the psychometric qualities of the Arabic version of the Scale of Coronavirus Anxiety (CAS) (EFA). 1188 participants, chosen by convenience sampling, are from six Arab nations: (391 participants from the Kingdom of Saudi Arabia), (257 from Egypt), (305) from Jordan, (135) from Bahrain, and 100 from the Sultanate of Oman. Of these, (389) participants are men and (799) are women. According to the EFA models, the data is represented by a one-dimensional structure that is dependable and invariant between genders. Similarly, CAS is more informative for high levels of COVID-19 anxiety, according to IRT data. The CAS in Arabic has adequate psychometric properties is a short measure to be used for COVID-19 anxiety.